Antiviral Steel Sheets Effective Against SARS-CoV-2 - Fumio Shibao (Corrosion science and technology, 2024)
In recent years, the awareness of infection prevention has increased owing to the spread of the novel coronavirus disease 2019. Antiviral products are necessary to avoid the risk of infection from existing and new SARS-CoV-2 variants. There is a growing need to impart antiviral properties to applications involving human contact. Therefore, antiviral steel sheets with a visible-light-responsive photocatalyst in the surface layer were developed in this study with intended applications on office furniture and interior finishing of buildings frequently touched by numerous people. The antiviral effect was investigated using a non-enveloped bacteriophage Q-beta (lipid bilayer membrane) and an enveloped SARS-CoV-2. A series of antiviral tests were conducted in compliance with JIS R 1756:2020 or by applying mutatis mutandis. Resistance of these antiviral steel sheets to sunlight was also investigated. These antiviral steel sheets developed in this study exhibited fingerprint resistance, formability, and antiviral properties. These sheets were also durable under exposure to sunshine. Thus, they can be used as an effective tool to reduce the risk of SARS-CoV-2 infection.